A dignidade da humanidade em kant : um estudo sobre a formação do caráter moral - Salomão, Jelson Becker (2013)
The present study deals with the formation of moral character according to Kant s pedagogical doctrine, taking the notion of dignity of humanity (Würde der Menschheit) as a guiding of the educational process. As a formative conception, founded on the idea of the autonomy of the will, Kant's pedagogical doctrine seeks to consolidate the moral character through respect for the dignity of humanity. To the extent that it involves multiple aspects of his philosophical system, the kantian pedagogical conception is defined as an anthropological application of a priori principles. Thus, it argues that the dignity of humanity constitutes a link between the formal and empirical dimensions of Kant's moral philosophy. The dignity of humanity as a regulative idea of practical reason is defined as a motive (Bewegunsgsgrund) to act from duty , not merely in conformity with duty . It means to say that the idea of the dignity of humanity is implicit in the formula of humanity, imposing duties to oneself, as well as duties to others. So, Kant argues the primacy of duties to oneself in relation to duties to others. In short, the idea of the dignity of humanity must be brought to the consciousness of the pupil in the process of formation of the moral character becoming a normative element of his moral conduct